Return to sport following surgical management of triangular fibrocartilage tears: a systematic review. Issue 1 (3rd April 2019) - Robertson, Greg; Ang, Kok Kiong; Maffulli, Nicola; Simpson, Claire K; Rust, Philippa A
Abstract: Introduction: This review aims to provide information on return rates and times to return to sport following surgical management of triangular fibrocartilage (TFC) tears. Sources of data: A systematic search of CINAHAL, Cochrane, EMBASE, Google Scholar, Medline, PEDro, Scopus, SPORTDiscus and Web of Science was performed using the keywords 'triangular', 'fibro-cartilage', 'complex', 'tear', 'distal radio-ulnar joint', 'athletes', 'sports', 'non-operative', 'conservative', 'operative' and 'return to sport'. Areas of agreement: In all of the 10 studies included, conservative management for 6 weeks to 6 months was the first-line treatment. If symptoms persisted following this period, surgical management was advised. Arthroscopic debridement was recommended for central tears, and arthroscopic repair was recommended for peripheral tears. Areas of controversy: The optimal treatment modalities for TFC tears remain to be defined. Growing points: Traumatic central tears can be treated with arthroscopic debridement alone. Arthroscopic repair with an all-inside repair can improve return rates to sport over an outside-in technique for ulna-sided tears. Areas timely for developing research: Future prospective studies should aim to establish the optimal treatment modalities for TFC tears.